PH, alkalinity, temperature, salinity and other variables collected from discrete sample and profile observations using Alkalinity titrator, CTD and other instruments from THALASSA in the North Atlantic Ocean from 2010-06-08 to 2010-06-30 (NODC Accession 0112842) - Mercier, H.; Rios, A.F., M. Ribas, M. VaÌzquez-RodriÌguez, M. CastanÌo, N. Fajar, F. F. PeÌrez, H. Mercier, V. Thierry, P. Branellec, P. Lherminier and P. Morin (NOAA NCEI Environmental Data Archive, 2016)
NCEI Accession 0112842 includes discrete sample and profile data collected from THALASSA in the North Atlantic Ocean from 2010-06-08 to 2010-06-30 and retrieved during cruise CLIVAR_OVIDE_2010. These data include DISSOLVED OXYGEN, HYDROSTATIC PRESSURE, NITRATE, Potential temperature (theta), SALINITY, TOTAL ALKALINITY (TA), WATER TEMPERATURE, pH, phosphate and silicate. The instruments used to collect these data include Alkalinity titrator, CTD, bottle and spectrophotometer. These data were collected by Aida F. Rios and Fiz Perez of Instituto de Investigaciones Marinas de Vigo and H. Mercier [affiliation unknown] as part of the CLIVAR_OVIDE_2010 data set. The International CLIVAR Global Ocean Carbon and Repeat Hydrography Program carries out a systematic and global re-occupation of select WOCE/JGOFS hydrographic sections to quantify changes in storage and transport of heat, fresh water, carbon dioxide (CO2), and related parameters.